Gregory Nazianzen’s Trinitarian Teaching Based on his Twentieth Theological Oration - Artemi, Eirini (De Medio Aevo, 2013)
Gregory of Nazianzus, the Theologian, is one of the most important fathers and saints of the Christianity, because of his theological thought and his intense poetical style in his work. He is thought as a writer of a unique beauty and brilliance in his writings. In his era, the teachings of Eunomius and Macedonius were a great threat for the Church. The apprehension of the divine nature, being pure spirit, is impossible for a materially based consciousness, and the only hope for human beings to have knowledge of God, therefore, is founded upon their ability to transcend material limitation, when the soul is invited back by God to its true spiritual nature and destiny (τέλος) in communion with God. This economy of salvation, described as a purification and ascent, determines from the outset the radically ‘economic’ nature of theology for Gregory. Gregory insists on explaining how the Holy Spirit exists, underlining that the way of the existence of every person of the Holy Trinity is unique for each of Them. The word ἴδιον (idion: specific) is used to show the relationship between the persons of the Triune God, and not their common nature. For this reason the names Father, Son and Holy Spirit are referred to their relationship, and not to οὐσία (ousia: essence). Also these names (Father, Son and Holy Spirit) do not show the actions of the Holy Persons, because they are common. Otherwise there would be the danger to the Son of not being God. He would be only a creature. For the first time, Gregory uses the unity of the persons of the Holy Trinity as a pattern of the unity of the two natures of incarnated Word, Christ. He uses this type of pattern, because Gregory saw the danger of the heretical teaching of Apollinarius. The latter supports that the human nature of Christ is absorbed by the divine one. Also, there is another heretical danger in thinking the recruitment of human nature by the divine one as superficial, false, not real. So the Christ would not be real Human and God and He could not save the human race. It is clear that Gregory’s trinitarian doctrine originates in a primary and profound soteriological imperative.